PLURALITAS AGAMA DAN KERUKUNAN UMAT BERAGAMA DI INDONESIA (Mencari Peran Pendidikan Agama di Perguruan Tinggi Umum) - Marzuki Marzuki (LPMPP Universitas Negeri Yogyakarta, 2001)
The inter-religious harmony should be done among the pluralistic society like Indonesia.Several ways can be made for building inter-religious harmony. The raising consciousness toappreciate religious freedom from adherents of a religion to others is a key for building thisharmony. To make the consciousness grows can be made with several ways, among them isreligious study method both by normative-theological approach and critical-empiricalapproach.The religious education in university, especially in public university, is one of mediumcan be made to do religious study for building inter-religious harmony. The religious educationcan be done by exclusive particularistic way for each adherent of a religion for martering hisreligious principles in depth. For building inter-religious harmony, the religious education willbe more effectively if it be done by pluralistic way, by participating all of the students fromseveral adherents of a religion to attend the study of religions. They are given thecomprehensive understanding to religions, especially about the equality, until they haveconsciousness to appreciate another religion with available.